Respostas
respondido por:
2
(2^2) ^3. (2^2) ^3 ÷(2^3) ^2=
2^6.2^`6:2^6=
2^12:2^6=
2^6
2^6.2^`6:2^6=
2^12:2^6=
2^6
respondido por:
3
OIá :)
x = (2²)³
y = (2²)³
z = (2³)²
Quando se está entre parênteses, multiplicamos os expoentes:
x = (2²)³ = 2.3 = 6 ⇒ = 64
y = (2²)³ = 2.3 = 6 ⇒ = 64
z = (2³)² = 3.2 = 6 ⇒ = 64
Substituindo os valores...
= = 64
Espero ter ajudado
x = (2²)³
y = (2²)³
z = (2³)²
Quando se está entre parênteses, multiplicamos os expoentes:
x = (2²)³ = 2.3 = 6 ⇒ = 64
y = (2²)³ = 2.3 = 6 ⇒ = 64
z = (2³)² = 3.2 = 6 ⇒ = 64
Substituindo os valores...
= = 64
Espero ter ajudado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás